Electrocatalytic SiC Nanoparticles/PEDOT:PSS Composite Thin Films as the Counter Electrodes of Dye‐Sensitized Solar Cells1. Issue 6 (13th March 2014) - Tsai, Yu‐Lin; Li, Chun‐Ting; Huang, Tzu‐Yen; Lee, Chi‐Ta; Lin, Chen‐Yang; Chu, Chih‐Wei; Vittal, R.; Ho, Kuo‐Chuan
Abstract A composite film consisting of silicon carbide nanoparticles and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (SiC‐NPs/PEDOT:PSS) is deposited on a fluorine‐doped tin oxide substrate and used as the counter electrode (CE) material for a dye‐sensitized solar cell (DSSC). The content of SiC is optimized to be 5 wt % with respect to PEDOT:PSS to obtain the best power conversion efficiency (η) of 7.25 % for the pertinent DSSC. The η of the best DSSC (7.25 %) is found to be slightly lower than that of the cell with a sputtered‐Pt CE (η=7.98 %). The films are characterized by using field‐emission scanning electron microscopy and energy‐dispersive X‐ray spectroscopy. Electrocatalytic parameters of the CEs are obtained by using cyclic voltammetry, rotating disk electrode, and Tafel polarization curves. Electrochemical impedance spectroscopy and incident photon‐to‐current conversion efficiency curves are used to substantiate the photovoltaic parameter.